2013
DOI: 10.1074/mcp.m112.019224
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics of Two Life Cycle Stages of Stable Isotope-labeled Trypanosoma brucei Reveals Novel Components of the Parasite's Host Adaptation Machinery

Abstract: Trypanosoma brucei developed a sophisticated life cycle to adapt to different host environments. Although developmental differentiation of T. brucei has been the topic of intensive research for decades, the mechanisms responsible for adaptation to different host environments are not well understood. We developed stable isotope labeling by amino acids in cell culture in trypanosomes to compare the proteomes of two different life cycle stages. Quantitative comparison of 4364 protein groups identified many protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
114
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 29 publications
6
114
0
Order By: Relevance
“…In contrast to PF, the BF cells do not contain a succinate-producing branch in their glycosomes (9) and hence exclusively regenerate the reduced cofactors required for glycolysis via the G3P:DHAP shuttle using mtG3PDH (13,14). The importance of mtG3PDH for the BF cells is further reflected by its upregulation compared to PF in this life stage at both the RNA level (42,43) and the protein level (44)(45)(46). The essentiality of mtG3PDH for BF is therefore not surprising, while depletion of the same protein in PF, reflected in the absence of its respective enzymatic activity, did not result in an altered growth phenotype, regardless of whether regular or lowglucose SDM-79 medium was used (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to PF, the BF cells do not contain a succinate-producing branch in their glycosomes (9) and hence exclusively regenerate the reduced cofactors required for glycolysis via the G3P:DHAP shuttle using mtG3PDH (13,14). The importance of mtG3PDH for the BF cells is further reflected by its upregulation compared to PF in this life stage at both the RNA level (42,43) and the protein level (44)(45)(46). The essentiality of mtG3PDH for BF is therefore not surprising, while depletion of the same protein in PF, reflected in the absence of its respective enzymatic activity, did not result in an altered growth phenotype, regardless of whether regular or lowglucose SDM-79 medium was used (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a comparative SILAC study, the putG3PDH protein was detected 5 times more often in PF than in BF (44), and yet two other studies using the same protein-labeling method failed to detect putG3PDH at all (45, 46) (see Table S4 in the supplemental material). Although this discrepancy might reflect different proteomics approaches, one cannot exclude the possibility that it has been influenced by the different cultivation media and strains used (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison to Whole-cell SILAC Proteomes-Three stage-specific whole-cell proteomes have been published (43)(44)(45). A detailed comparison to the Urbaniak et al (44) and Butter et al (43) studies is shown in Fig.…”
Section: Enrichment In the Bound Versus Input Or Unboundmentioning
confidence: 99%
“…5B). For Butter et al (43), replicate protein ratios from supplemental Table S3 in (43) were converted to Log 2 (PCF/BSF) and averaged. Urbaniak et al (44) reported 10.6% of their whole cell proteome to be fivefold differentially expressed between the BSF and PCF life cycle stages.…”
Section: Enrichment In the Bound Versus Input Or Unboundmentioning
confidence: 99%
“…However, mRNAs are further translated into proteins, which perform the actual cellular functions. It has been shown in multiple species such as Saccharomyces cerevisiae (Griffin et al 2002), Trypanosoma brucei (Butter et al 2013), Caenorhabditis elegans (Grün et al 2014), and human (Schwanhäusser et al 2011), as well as in Drosophila melanogaster (Bonaldi et al 2008), that transcript levels are only a moderate predictor for protein expression as they do not account for post-transcriptional processes such as translational regulation or protein stability (Vogel and Marcotte 2012;Liu et al 2016). Recently, this has also been addressed with a developmental perspective in Caenorhabditis elegans (Grün et al 2014), Xenopus laevis (Peshkin et al 2015), and Trypanosoma brucei (Dejung et al 2016), but not yet in Drosophila.…”
mentioning
confidence: 99%